Inspiratory muscle load and capacity in chronic heart failure. Issue 6 (28th May 2004) - Hart, N; Kearney, M T; Pride, N B; Green, M; Lofaso, F; Shah, A M; Moxham, J; Polkey, M I
Abstract : Background: Although breathlessness is common in chronic heart failure (CHF), the role of inspiratory muscle dysfunction remains unclear. We hypothesised that inspiratory muscle endurance, expressed as a function of endurance time (Tlim) adjusted for inspiratory muscle load and inspiratory muscle capacity, would be reduced in CHF. Methods: Endurance was measured in 10 healthy controls and 10 patients with CHF using threshold loading at 40% maximal oesophageal pressure (Poesmax ). Oesophageal pressure-time product (PTPoes per cycle) and Poesmax were used as indices of inspiratory muscle load and capacity, respectively. Results: Although Poesmax was slightly less in the CHF group (−117.7 (23.6) v −100.0 (18.3) cm H2 O; 95% CI −37.5 to 2.2 cm H2 O, p = 0.1), Tlim was greatly reduced (1800 v 306 (190) s; 95% CI 1368 to 1620 s, p<0.0001) and the observed PTPoes per cycle/Poesmax was increased (0.13 (0.05) v 0.21 (0.04); 95% CI −0.11 to −0.03, p = 0.001). Most of this increased inspiratory muscle load was due to a maladaptive breathing pattern, with a reduction in expiratory time (3.0 (5.8) v 1.1 (0.3) s; 95% CI 0.3 to 3.5 s, p = 0.03) accompanied by an increased inspiratory time relative to total respiratory cycle (Ti/Ttot) (0.43 (0.14) v 0.62 (0.07); 95% CI −0.3 to −0.1, p = 0.001). However, log Tlim, which incorporates the higher inspiratory muscle load to capacity ratio caused by this altered breathing pattern, was ⩾85% predicted in seven of 10 patients. Conclusions: Although a marked reduction in endurance time was observed in CHF, much of this reduction was explained by the increased inspiratory muscle load to capacity ratio, suggesting that the major contributor to task failure was a maladaptive breathing pattern rather than impaired inspiratory muscle endurance.